Comparative Genome Analysis Reveals Phylogenetic Identity of Bacillus velezensis HNA3 and Genomic Insights into Its Plant Growth Promotion and Biocontrol Effects - Zaid, Doaa S.; Cai, Shuyun; Hu, Chang; Li, Ziqi; Li, Youguo (Microbiology spectrum, 2022)
This study is the primary initiative to identify Bacillus velezensis HNA3 whole genome sequence and reveal its genomic properties as an effective biocontrol agent against plant pathogens and a plant growth stimulator. HNA3 genetic profile can be used as a reference for future studies that can be applied as a highly effective biofertilizer and bio fungicide inoculum to improve agriculture productivity. Bacillus velezensis HNA3, a potential plant growth promoter and biocontrol rhizobacterium, was isolated from plant rhizosphere soils in our previous work. Here, we sequenced the entire genome of the HNA3 strain and performed a comparative genome analysis. We found that HNA3 has a 3,929-kb chromosome with 46.5% GC content and 4,080 CDSs. We reclassified HNA3 as a Bacillus velezensis strain by core genome analysis between HNA3 and 74 previously defined Bacillus strains in the evolutionary tree. A comparative genomic analysis among Bacillus velezensis HNA3, Bacillus velezensis FZB42, Bacillus amyloliquefaciens DSM7, and Bacillus subtilis 168 showed that only HNA3 has one predicated secretory protein feruloyl esterase that catalyzes the hydrolysis of plant cell wall polysaccharides. The analysis of gene clusters revealed that whole biosynthetic gene clusters type Lanthipeptide was exclusively identified in HNA3 and might lead to the synthesis of new bioactive compounds. Twelve gene clusters were detected in HNA3 responsible for the synthesis of 14 secondary metabolites including Bacillaene, Fengycin, Bacillomycin D, Surfactin, Plipastatin, Mycosubtilin, Paenilarvins, Macrolactin, Difficidin, Amylocyclicin, Bacilysin, Iturin, Bacillibactin, Paenibactin, and others. HNA3 has 77 genes encoding for possible antifungal and antibacterial secreting carbohydrate active enzymes. It also contains genes involved in plant growth promotion, such as 11 putative indole acetic acid (IAA)-producing genes, spermidine and polyamine synthase genes, volatile compound producing genes, and multiple biofilm related genes. HNA3 also has 19 phosphatase genes involved in phosphorus solubilization. Our results provide insights into the genetic characteristics responsible for the bioactivities and potential application of HNA3 as plant growth-promoting strain in ecological agriculture. IMPORTANCE This study is the primary initiative to identify Bacillus velezensis HNA3 whole genome sequence and reveal its genomic properties as an effective biocontrol agent against plant pathogens and a plant growth stimulator. HNA3 genetic profile can be used as a reference for future studies that can be applied as a highly effective biofertilizer and biofungicide inoculum to improve agriculture productivity. HNA3 reclassified in the phylogenetic tree which may be helpful for highly effective strain engineering and taxonomy. The genetic comparison among HNA3 and closely similar species B. velezensis FZB42, B. amyloliquefaciens DSM7, and B. subtilis 168 demonstrates some distinctive genetic properties of HNA3 and provides a basis for the genetic diversity of the Bacillus genus, which allows developing more effective eco-friendly resources for agriculture and separation of Bacillus velezensis as distinct species in the phylogenetic tree.